ANALISIS PEMILIHAN SUPPLIER BATU BATA MERAH DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Fauziah, Nur Elliza (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Selecting the correct supplier can make company’s safety price and earnings remain the same and more stable. Correct suppliers also ensure quality products as the raw materials are more consistent. The goal of this research is to choose the correct red brick supplier for Griya Andalusia Malang, a housing developer. Here Analytical Hierarchy Process was used to help multi-criteria decision making; the criteria were arranged in a subjective hierarchical order to get alternatives with the highest priority weight. Using judgmental sampling, five experts in supplier selection were involved as informants, from whom data was harvested through interviews. The results of the data analysis suggest that UD. ABC should be prioritized in red brick supply, followed by UD. MNO and UD. XYZ. The finding can be used by Griya Andalusia Malang to determine their red brick supplier.